Transformasi Sosial Ekonomi Masyarakat Peri-Urban di Sekitar Pengembangan Lahan Skala Besar: Kasus Bumi Serpong Damai - Maulien Kharina Sari; Haryo Winarso (Journal of Regional and City Planning, 2007)
Large scale land development in outer skirt of a city brings some impacts in its surrounding areas. One of them is related to the per-urbanization process. The development in not only transforming its own area, but also changing its surrounding. The development changes the land uses, creates certain concentrations and changes the surrounding area from predominantly rural characteristics, to peri-urban characteristics, an area with combination of rural and urban characteristics. This study explains the socio-economic transformation of the people living close to large scale land development of BSD. The result shows that socio-economic conditions of the people have been significantly transformed, especially in migration, jobs, income and spending of household's variables. The transformation can be seen from increase of the proportion of migrants; change in the job's structure; the increasing number of secondary and tertiary sectors jobs, the increasing household's income, and the increasing of household's spending for non-primary needs. The transformation is triggered by land development in BSD, such as the growth of industries and commercial activities in BSD which create job opportunities and attract people to migrate the surrounding of BSD.Keywords: large-scale land development, peri-urban, socio-economic transformation, BSD